2023
DOI: 10.3390/agronomy13020604
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Low Nitrogen Tolerance in Oat (Avena sativa L.) Seedlings

Abstract: In oat production, the over-application of nitrogen (N) fertilizer in fields due to low N fertilizer use efficiency not only increases production costs but also causes environmental pollution. Currently, mining low N-tolerant oat varieties is an important way to promote sustainable agriculture. In this study, 30 oat varieties were grown in a seedling culture with two treatments of normal N (10 mM NH4NO3) and low N (1.25 mM NH4NO3), and the correlations between agronomic traits and plant N content and low N tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our study found some AsTCP genes (19 genes, about 39%) did not contain introns. This structural feature is similar to that found in Camellia sinensis (87%) ( Shang et al., 2022 ), Cymbidium goeringii (57%) ( Liu D. et al., 2022 ), and Dactylis glomerata (18%) ( Wang C. et al, 2023 ). Most AsTCP genes do not have introns, meaning their transcription times are shorter than those containing introns.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study found some AsTCP genes (19 genes, about 39%) did not contain introns. This structural feature is similar to that found in Camellia sinensis (87%) ( Shang et al., 2022 ), Cymbidium goeringii (57%) ( Liu D. et al., 2022 ), and Dactylis glomerata (18%) ( Wang C. et al, 2023 ). Most AsTCP genes do not have introns, meaning their transcription times are shorter than those containing introns.…”
Section: Discussionsupporting
confidence: 83%
“…After seedlings grew to 3 weeks of age, we divided seedlings into two groups. One group was treated with Hoagland nutrient solution containing 1.25 mM NH 4 NO 3 for low nitrogen stress (LN- Low nitrogen), and the other group was incubated with Hoagland nutrient solution holding 10 mM NH 4 NO 3 (NN-normal nitrogen) ( Wang Y. et al., 2023 ). The low N treatment time points were 7 and 14 days, with a control group at normal N levels.…”
Section: Methodsmentioning
confidence: 99%
“…For a more comprehensive assessment of plant stress resistance, employing multidimensional indices is considered more scientifically sound ( Wu et al., 2019 ; Weng et al., 2021 ). Membership function analysis has gained a wider use in recent years for evaluating plant stress tolerance in that it addresses the limitations of selecting plant varieties based on a single index ( Wassie et al., 2019 ; Weng et al., 2021 ; Wang et al., 2023 ). In the present study, through membership function analysis, 14 individual indicators were integrated into a comprehensive evaluation index of salt tolerance (D value) for different genotypes of M. sacchariflorus and M. lutarioriparius at the seedling stage, with a higher D value indicating stronger salt tolerance ability.…”
Section: Discussionmentioning
confidence: 99%
“…The salt tolerance of M. sacchariflorus and M. lutarioriparius was evaluated by calculating the membership function value (MFV) of STI and traits such as RGR, RNIL, RLER, Sen, SWC, RWC, SNC, RNC, SN/RN, SKC, RKC, SK/RK, SK/N, and RK/N using a fuzzy comprehensive evaluation method. The MFV of salt tolerance was calculated using the following equation ( Wassie et al., 2019 ; Weng et al., 2021 ; Wang et al., 2023 ):…”
Section: Methodsmentioning
confidence: 99%